Trace-Element Geochemistry of Sulfides in Upper Mantle Lherzolite Xenoliths from East Antarctica - Alexandre V. Andronikov; Irina E. Andronikova; Tamara Sidorinova (Minerals, 2021)
Sulfides in upper mantle lherzolite xenoliths from Cretaceous alkaline-ultramafic rocks in the Jetty Peninsula (East Antarctica) were studied for their major and trace-element compositions using SEM and LA-ICP-MS applied in situ. Modal abundance of sulfides is the lowest in Cpx-poor lherzolites ≤ Spl-Grt lherzolites << Cpx-rich lherzolites. Most sulfides are either interstitial (i-type) or inclusions in rock-forming minerals (e-type) with minor sulfide phases mostly present in metasomatic veinlets and carbonate-silicate interstitial patches (m-type). The main sulfide assemblage is pentlandite + chalcopyrite ± pyrrhotite; minor sulfides are polydymite, millerite, violarite, siegenite, and monosulfide solution (mss). Sulfide assemblages in the xenolith matrix are a product of the subsolidus re-equilibration of primary mss at temperatures below ≤300 °C. Platinum group elements (PGE) abundances suggest that most e-type sulfides are the residues of melting processes and that the i-type sulfides are crystallization products of sulfide-bearing fluids/liquids. The m-type sulfides might have resulted from low-temperature metasomatism by percolating sulfide-carbonate-silicate fluids/melts. The PGE in sulfide record processes are related to partial melting in mantle and intramantle melt migration. Most other trace elements initially partitioned into interstitial sulfide liquid and later metasomatically re-enriched residual sulfides overprinting their primary signatures. The extent of element partitioning into sulfide liquids depends on P, T, fO2, and host peridotite composition.